Chancay Bay Environmental Recovery Plan - Cabrera Carranza, Carlos Francisco (2003)
The environmental recovery of coastal ecosystems is an environmental management initiative for consultation among the main actors in the development of a city. This work presents an environmental recovery proposal that includes certain management instruments, aimed at reversing the situation of environmental degradation of the coastal waters of Chancay Bay. Due to the importance of the town of Chancay at the regional level and due to the complexity of its environmental problems, this proposal constitutes an alternative of environmental management that can be taken into account in other coastal areas of our territory.